Pro‐glacial lake sedimentation from jökulhlaups (GLOF), Blåmannsisen, northern Norway. Issue 5 (7th November 2014) - Xu, Mengzhen; Bogen, Jim; Wang, Zhaoyin; Bønsnes, Truls E.; Gytri, Stine
Abstract Outburst floods from glacier‐dammed lakes are major events associated with glacier thinning and volume reduction. This paper investigates jökulhlaups emanating from the glacier‐dammed lake Øvre Messingmalmvatn at Rundvassbreen, an outlet glacier of the Blåmannsisen ice cap in northern Norway. Since 2001, the lake has several times been observed to drain suddenly, causing jökulhlaup outbursts into the pro‐glacial lake Rundvatnet. Varve analysis and lead‐210 (210Pb) dating were used to date sediment cores taken from Rundvatnet. It was found that sedimentation from jökulhlaups is recognizable in the lake as distinct sand layers embedded in the varved silt‐clay sequence which represents the normal lake sedimentation. Sand fractions were carried in suspension because of the extreme hydraulic conditions of jökulhlaups. The thickest sand layer was deposited during the 2001 jökulhlaup which lasted three days and had a total volume of 40 ×106 m3. Jökulhlaups were also recorded in 2005, 2007, 2009, and 2010; they each resulted in a sand layer. Annual sediment accumulation in Rundvatnet increased up to 10‐fold during the years with jökulhlaup outburst floods, from a normal value of 1–2 mm yr−1 to 8–10 mm yr−1. Five other jökulhlaups were identified from the 1910–1930 sedimentation interval, in addition to those observed in 2001–2010; there appear to have been none for 70 years during 1931–2000. Each jökulhlaup was preceded by a period when the glacier thinned to a critical volume and could no longer withstand the hydrostatic pressure of Øvre Messingmalmvatn; consequently a tunnel developed beneath the glacier, leading to a jökulhlaup. Statistical analyses of the correlations between the pro‐glacial sedimentation rate and temperature and precipitation suggested that although climate conditions are expected to influence sedimentation in the pro‐glacial catchment, a host of other interacting factors moderate the availability and delivery of sediment to the pro‐glacial system, making the processes responsible for changes in pro‐glacial sedimentation to remain uncertain. Copyright © 2014 John Wiley & Sons, Ltd.